Institutionalized violence in schools and language displacement: the voices of Mapuche speakers and elders - Sanhueza, Susan; Maldonado, Fabiola; Díaz, Claudio; Friz, Miguel; Toloza, Carolina Aroca; Cuevas, Hector Torres (Frontiers in Psychology, 2025)
This article addresses language displacement as a result of the institutionalized violence experienced by the Mapuche people. The objective is to explore, through the voices of Mapuche speakers and elders, the institutionalized violence encountered in schools and its impact on the displacement of the Mapuzungun language. Through discussion groups, we explored ancestral knowledge, language loss, its intergenerational transmission, and how the teaching of Mapuzungun should be approached for future generations. The results show that the elders possess an immeasurable source of knowledge, being the primary bearers of the culture, and propose an epistemology centered on the unity of language and culture.